The Effect of Tax Risk on Tax Avoidance - Yenni Mangoting; Oviliani Yenty Yuliana; Jesslyn Effendy; Lovena Hariono; Viennie Melinda Lians (University of Merdeka Malang, 2021)
This research intends to investigate whether tax risk is associated with tax avoidance, which is proxied by Cash Effective Tax Rate (CETR). Tax risk is measured by six tax risk components: transactional risk, compliance risk, operational risk, financial accounting risk, managerial risk, and reputational risk. The samples in this research are manufacturing companies listed on the Indonesian Stock Exchange (IDX). With a purposive sampling method, there are 168 firm years which we analyzed with OLS regression. The result in this study showed that tax risk is positively associated with CETR. It implied that choices of tax strategies and activities are involved in high tax risk, but firms still choose to comply with tax regulations, which can be seen in high CETR values. This research found that firms need tax risk management to ensure that tax strategies do not impact the firms’ future losses from additional tax payments and fines. Other than that, this research gives a new option for future researchers to measure tax risk using scoring methods and indicators that are engaged in each of the tax risk components.DOI: 10.26905/jkdp.v25i3.5629